(3GdLhGgQ hGdOQQ aj efGbH TjN GdESdGe GHf MLQs - (3Yde GdOjf Ydj Hf eMeO GdSNGhj,J (B643 (3g` s
(3BNQgG (B:s
(3hjbhd GfRd jGSjOi Edi SGYI Cbh eYc aSFd abGd gPG SYjO Hf GdeSj LGfi hNQLJ QhMg NJe Gddg GeGdfG HGdUGdMGJ GdecQ hgh ZQGQ cKjQ hGdePgHI ai GdHSedI s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B332s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs